OS14.6.A GlioCova: Defining patient safety events for brain tumour patients undergoing neurosurgery. (9th September 2021) - Mauricaite, R; Le Calvez, K; Brodbelt, A; Bottle, A; Williams, M
Abstract: BACKGROUND: Surgery is associated with a risk of adverse events (e.g. venous thrombosis). These have been used to define the OECD Patient Safety Event (PSE) indicators (41 diagnostic codes), but not in the brain tumour population. The GlioCova project uses English linked national cancer data on all 51, 775 adult primary brain tumour patients (2013–2018). MATERIAL AND METHODS: We identified all glioblastoma patients having surgery for their tumour and noted the 100 most common ICD-10 diagnostic codes within 30 days of surgery, excluding previous medical conditions, brain tumour diagnosis codes and OECD-defined codes. Potential post-surgical complications were reviewed by a group of experienced clinicians. We reviewed these "novel PSE codes" in all brain tumour patients re-admitted after surgery. We looked at the co-occurrence between our novel and OECD codes and combined them to form the final PSE list.Patients readmitted within 30 days were divided into those without codes ("PSE-free"), and those with at least one PSE code during admission or readmission. We examined age, length of stay, in-hospital and 30-day mortality and assessed statistical significance using Welch's t-test and a two sample Z-test for proportions. RESULTS: 29, 135 patients underwent neurosurgery, of whom 8, 361 (28.7%) were readmitted within 30 days. We identified 32 novel PSE codes. 1, 319 (16%) patients had an OECD code, 5, 524 (66%) had a novel code, and 2, 098 (25%) patients were PSE-free. 83% of patients who had an OECD PSE code also had a novel code. Patients in the PSE group were older (median age = 60 years) than the PSE-free group (57 years). Length of stay was longer in patients who had a PSE after surgery (median = 7 days) and after readmission (5 days) compared with PSE-free after surgery (4 days), at readmission (0 days). More patients died in hospital after readmission in the PSE group (4.7%) compared with no-PSE (2.7%). 30-day mortality after surgery was similar in both groups (2.5% PSE-free, 3.1% PSE group). All differences were highly statistically significant (p<0.0001). CONCLUSION: We identified 32 novel patient safety event codes following surgery in the brain tumour population. Patients with these diagnostic codes had an elevated LOS and in-hospital death rate. Using brain tumour specific PSE codes captures many more events than the existing list of OECD codes.